Morphology, Volume, and Density Characteristics of the Parotid Glands before and after Chemoradiation Therapy in Patients with Head and Neck Tumors - Wellington Pereira dos Santos; João Pedro Perez Gomes; Amanda Drumstas Nussi; João Mauricio Altemani; Maria Teresa Botti Rodrigues dos Santos; Bengt Hasseus; Daniel Giglio; Paulo Henrique Braz-Silva; Andre Luiz Ferreira Costa (International Journal of Dentistry)
The multimodal approach for patients with head and neck cancer (HNC) includes treatment with chemoradiation therapy (CRT). A common concern regarding CRT side effects is the occurrence of structural and physiological alterations of the salivary glands due to exposure to ionizing radiation. The aim of this study is to examine the morphology, volume, and density of the parotid glands before and after CRT in HNC patients. A total of 49 HNC patients treated exclusively with CRT were included in the study. Ninety-eight parotid glands were evaluated before and after treatment by using contrast-enhanced computed tomography (CECT). Shapiro–Wilk test was performed, and the variables (pre-CRT and post-CRT) presented normal distribution. Pearson’s coefficient was used to assess the correlation between volume and density. CRT resulted in a significant decrease in the mean volume of the parotid glands (i.e., original volume reduced by 20.5%; P<0.0001). CRT induced a 30.0% (7 Hounsfield units) increase in density of the right parotid gland and a 24.9% (8 Hounsfield units) increase in density of the left parotid gland (P=0.0198 and P=0.0079, respectively). Changes in morphology and spatial configuration, increased density, and substantial loss of volume of the parotid glands were observed after CRT. There was also a difference in density (P=0.003) in the right-side parotid glands in comparison between xerostomic and nonxerostomic groups of patients. These facts lead to the need for a personalized CRT planning in order to minimize oral complications related to the treatment.